Mechanical Performance and Failure Mode Research on the Braced Frame Joint of Tower Cranes in High-Rise Building Construction - Yang, Yang; Zhang, Zhen; Xu, Liangjin; Yao, Gang (Frontiers in Materials, 2022)
The collapse number of tower crane springs out with development of building industry. Safety of tower crane has the potential to improve practices of building and outcomes in construction. The mechanical performance and failure mode of braced frame joint are analyzed in this research. Firstly, the mechanical model of braced frame joint (BFJ) is established, and the experiment is designed. The destruction process and failure mode are researched by experiment. Then finite element model is established by ABAQUS. Moreover, working conditions with different concrete strength grade (CSG) and tension direction are researched. The results prove that BFJ cracks seriously with ultimate bearing capacity, simultaneously, pre-embedded steel component (PESC) is pulled out. The failure mode is tensile and bending failure of BFJ in the test. The ultimate bearing capacity of failure is controlled by CSG. The tensile strength increases with the CSG, and the ultimate capacity of BFJ improves equally. The brittle fracture characteristic is more obvious in ultimate state. The failure mode changes from crushing failure to tensile and bending failure with increasing of tension angle. The research results could provide a better understanding for working mechanism and performance evaluation of BFJ of tower crane.